2020
DOI: 10.1111/ssqu.12772
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Motivations for Joining Unions: The Role of Prosocial Beliefs

Abstract: Objective This article investigates whether a prosocial orientation—which stresses unions’ concern for all working people—might differentially influence whites’ and African Americans’ decisions to join unions. Methods Logistic regression using data from the 2005 AFL‐CIO Union Message Survey. Results African Americans’ odds of voting “yes” in a hypothetical union election are nearly two times greater than whites’ odds, and prosocial beliefs partially mediate this effect. Conclusion A model of unionism that seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Specifically, compared to White respondents, Black respondents perceived the risk of COVID-19 to be greater to others and both Black and Latinx respondents thought it was more important to protect groups of non-close others (e.g., people who live in your city and state). The roots of Black-White differences in prosocial beliefs may, in part, stem from more prosocial and collectivist worldviews because of Black people’s involvement in civil rights struggles and greater engagement in church and working in the public sector [ 24 ]. The differences may also have an underlying logic similar to the White (and Asian) male effect—a robust pattern where some White and Asian men express less concern about a range of threats to society such as technology, climate change and other environmental threats, guns, and crime [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, compared to White respondents, Black respondents perceived the risk of COVID-19 to be greater to others and both Black and Latinx respondents thought it was more important to protect groups of non-close others (e.g., people who live in your city and state). The roots of Black-White differences in prosocial beliefs may, in part, stem from more prosocial and collectivist worldviews because of Black people’s involvement in civil rights struggles and greater engagement in church and working in the public sector [ 24 ]. The differences may also have an underlying logic similar to the White (and Asian) male effect—a robust pattern where some White and Asian men express less concern about a range of threats to society such as technology, climate change and other environmental threats, guns, and crime [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…People favoring the Democratic Party expressed more favorable union attitudes, greater likelihood of union approval, and a greater inclination to vote for union representation. Some race/ethnic effects were present, with Blacks evidencing a more positive general attitude to unions and a greater likelihood of voting for union representation (see also Gumber and Padavic 2020). Southerners were less likely to approve of unions.…”
Section: Resultsmentioning
confidence: 98%
“…More recently, a review by Fiorito et al (2018) and an empirical study using survey data (Fiorito and Padavic, in press) suggested that prosocial motivations may be an underappreciated influence on union voting intent and other forms of union support in the US. Another recent study of African-American workers’ motivations highlighted the greater importance of prosocial motivations in their positive assessment than in whites’ (Gumber and Padavic, 2020).…”
Section: Theory and Hypotheses On Union Support And Voting Intentionsmentioning
confidence: 99%